Depth‐resolved investigation of multiple optical properties and wrinkle morphology in eye‐corner areas with multi‐contrast Jones matrix optical coherence tomography. Issue 3 (27th October 2020) - Yamazaki, Kohei; Li, En; Miyazawa, Arata; Kobayashi, Masaki; Sayo, Tetsuya; Makita, Shuichi; Takahashi, Yoshito; Yasuno, Yoshiaki; Sakai, Shingo
Abstract: Background: Multi‐contrast Jones matrix optical coherence tomography (JM‐OCT) can provide quantitative depth‐resolved local optical properties by improving the measurement algorithm. Materials and methods: We examined the relationship between depth‐resolved local optical properties of eye‐corner skin measured by JM‐OCT and corresponding wrinkle morphology of aged women (n = 21; age range, 71.7 ± 1.7 years). Wrinkle morphology was analyzed by measuring the surface topography of three‐dimensional replicas. The same regions were measured three‐dimensionally by JM‐OCT, and the local optical properties at each depth were computed. Results: Birefringence (BR) and mean wrinkle depth correlated significantly at a depth of 88.2‐138.6 µm from the skin surface, and attenuation coefficient (AC) and mean wrinkle depth correlated significantly at a depth of 12.6‐18.9 µm and 189‐459.9 μm from the skin surface, although a degree of polarization uniformity (DOPU) did not. Stepwise multiple regression analysis demonstrated that a significant regression equation ( R 2 = 0.649, P < .001) for predicting mean wrinkle depth was determined by BR at 107.1 µm depth (BR 107.1 µm ), DOPU at 170.1 µm (DOPU 170.1µm ), and AC at 252 µm (AC 252 µm ) as independent variables and that these standardized beta regression coefficients were −0.860, −0.593, and −0.440, respectively, suggesting that BR, DOPU, and AC sufficiently explained mean wrinkle depth. Conclusion: These results suggest that BR 107.1 µm, DOPU 170.1 µm, and AC 252 µm may indicate collagen‐related structure in the papillary, upper‐reticular dermis, and microstructure or tissue density in reticular dermis, respectively, and may be involved in wrinkle formation.